Genetically attenuated P36p-deficient Plasmodium berghei sporozoites confer long-lasting and partial cross-species protection - Douradinha, Bruno (2021)
© 2007 Australian Society for Parasitology Inc. Published by Elsevier Ltd. All rights reserved.